2019
DOI: 10.1021/acs.est.9b04626
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic vs Coastal—Key Drivers of Pollutant Levels in Barents Sea Polar Bears with Contrasted Space-Use Strategies

Abstract: In the Barents Sea, pelagic and coastal polar bears are facing various ecological challenges that may explain the difference in their pollutant levels. We measured polychlorinated biphenyls, organochlorine pesticides, polybrominated diphenyl ethers in fat, and perfluoroalkyl substances in plasma in pelagic and coastal adult female polar bears with similar body condition. We studied polar bear feeding habits with bulk stable isotope ratios of carbon and nitrogen. Nitrogen isotopes of amino acids were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 95 publications
1
16
0
Order By: Relevance
“…177,179,180 A comparison of selected polar bears with similar body conditions in the Barents Sea, showed that offshore polar bears were exposed to higher concentrations of pollutants than coastal bears and that this was related to differences in feeding habits, energy expenditure, and geographical distribution. 41 Nonetheless, since offshore bears were, on average, fatter than coastal ones, 181,182 plasma concentrations of lipophilic POPs were overall similar in bears with different strategies, and only proteinophilic PFASs were higher in pelagic bears. 181 Compound-specic and bulk stable isotopes (d 15 N and d 13 C), home range, eld metabolic rates (based on telemetry), as well as contaminant levels in harp seal prey from different locations, cumulatively indicated that higher POP concentrations in offshore Barents Sea polar bears were related to a combination of factors, including the consumption of greater proportions of high-trophic level and marine-based prey, higher levels of POPs in prey species, larger energy requirements, and distribution in marginal ice zones (Fig.…”
Section: C4 Behavioral Changes Related To Sea Ice Covermentioning
confidence: 97%
See 2 more Smart Citations
“…177,179,180 A comparison of selected polar bears with similar body conditions in the Barents Sea, showed that offshore polar bears were exposed to higher concentrations of pollutants than coastal bears and that this was related to differences in feeding habits, energy expenditure, and geographical distribution. 41 Nonetheless, since offshore bears were, on average, fatter than coastal ones, 181,182 plasma concentrations of lipophilic POPs were overall similar in bears with different strategies, and only proteinophilic PFASs were higher in pelagic bears. 181 Compound-specic and bulk stable isotopes (d 15 N and d 13 C), home range, eld metabolic rates (based on telemetry), as well as contaminant levels in harp seal prey from different locations, cumulatively indicated that higher POP concentrations in offshore Barents Sea polar bears were related to a combination of factors, including the consumption of greater proportions of high-trophic level and marine-based prey, higher levels of POPs in prey species, larger energy requirements, and distribution in marginal ice zones (Fig.…”
Section: C4 Behavioral Changes Related To Sea Ice Covermentioning
confidence: 97%
“…Studies from the Barents Sea have reported higher levels of lipophilic POPs and per-and polyuoroalkyl substances (PFASs) in polar bears (Ursus maritimus) that use high-quality sea ice habitats (i.e., the marginal ice zone) in eastern Svalbard/Barents Sea, compared to bears using habitats with less or no sea ice in western Svalbard. [38][39][40][41] These differences may be inuenced by the presence/absence of sea ice, 14 in addition to other biotic factors, which are discussed in Section C. The presence of sea ice is likely to increase uptake of atmospherically-deposited POPs into the marine food web. For example, PFASs deposited on surface snow are released and concentrated into the meltwater at the base of the snowpack by the end of the melting period, 42 which is followed by phytoplankton bloom and subsequently large increases of zooplankton biomass.…”
Section: B3 Sea Icementioning
confidence: 99%
See 1 more Smart Citation
“…The whale FGs with SI data in this study included baleen and toothed whales and long distance seasonal migrants (blue whales, fin whales, minke whales) and all-year resident whales in the Barents Sea (e.g., harbor porpoise and killer whales). Individual feeding specialization was found for killer whales and polar bears (Blévin et al, 2019;Jourdain et al, 2020). Some killer whales specialize in feeding on coastal seals and show high δ 15 N values while the majority of the individuals feed on herring (Jourdain et al, 2020), and have relatively low δ 15 N values and low standard deviation of δ 15 N value (SD = 0.05) (Supplementary Table 4).…”
Section: Comparison Of Trophic Positions Estimated From Ecopath and L...mentioning
confidence: 99%
“…Southern populations in close proximity to human settlements, typically carry heavier pollutant loads compared to their northern counterparts. Heavy contaminant loads in marine mammals are associated with compromised immune systems, hormonal disruptions and increased parasite burden [204][205][206]. Although few major sources of pollution typically originate in the Arctic, this region is nevertheless exposed to pollutants through atmospheric and marine transport and freshwater runoff.…”
Section: Increased Anthropogenic Disturbances May Affect Pristine Popmentioning
confidence: 99%